Indians in Unexpected Places - Deloria, Philip Joseph (Book collections on Project MUSE., 2004)
"Despite the passage of time, our vision of Native Americans remains locked up within powerful stereotypes. That's why some images of Indians can be so unexpected and disorienting: What is Geronimo doing sitting in a Cadillac? Why is an Indian woman in beaded buckskin sitting under a salon hairdryer? Such images startle and challenge our outdated visions, even as the latter continue to dominate relations between Native and non-Native Americans." "Philip Deloria explores this cultural discordance to show how stereotypes and Indian experiences have competed for ascendancy in the wake of the military conquest of Native America and the nation's subsequent embrace of Native "authenticity." Rewriting the story of the national encounter with modernity, Deloria provides revealing accounts of Indians doing unexpected things - singing opera, driving cars, acting in Hollywood - in ways that suggest new directions for American Indian history."--Jacket.